Critical Reflexivity of the Researcher as an Exploratory Vehicle in Sensitive Research - Rineeta Banerjee; Manisha Dasgupta (Journal of Psychosexual Health)
Qualitative research requires in-depth immersion in the topic of concern for the findings to be valid and pertinent. However, in doing so, qualitative researchers may encounter certain challenges that address beyond the methodological concern. There is limited research that explores the impact on researchers who undertake research on sensitive or challenging research and marginalized groups. Considering that the researcher is the central figure who influences the research project across all steps from conceptualization to action, researcher reflexivity can be used as a strategy to look behind the curtain of the research project. Through practicing critical reflexive experiential analysis, I reflect on my journey on conducting research on the topic of sexual violence. I address the silence of researcher vulnerability by documenting and analyzing my emotional journey through each stage of the research project in my reflexive journal and how I resolved each dilemma at both personal and professional levels. The aim of this article is, therefore, to highlight the process of critical reflexivity of my journey as a sexual violence researcher in Indian context.